Manajemen Electronic Government Dalam Pelayanan Administrasi Kependudukan Di Kantor Dinas Kependudukan Dan Pencatatan Sipil Kota Palu - Natalia, Desi; Hattab, Syahruddin; Mayusa, Askar (JPS: Journal of Publicness Studies, 2025)
This study aims to determine the management of e-government in population administration services at the Population and Civil Registration Office of Palu City using a qualitative descriptive method based on the four principles of management according to George R. Terry, with 4 (four) aspects of planning, organizing, implementing, and monitoring. Data were collected through observation, interview, and documentation. The results showed that despite progress in strategic planning in separating manual and electronic-based service systems, the implementation of e-government still faces obstacles, such as the absence of a formal organizational structure, unclear division of tasks, technical problems, lack of guidance for users, and lack of training for human resources. Supervision has been carried out through monitoring, satisfaction surveys, and online complaints, but still needs to be improved. Therefore, improvements in the aspects of organization and implementation are needed so that the benefits of e-government services can be optimally felt by the community.